Analisis Industri Pengolahan Susu di Indonesia - lim Sanny (Binus Business Review, 2011)
Milk is the main food for all ages. In addition, many products can be made from milk such as food, beverages, cheese, butter, yogurt, etc.. Opportunities milk processing industry in Indonesia is very good, considering that Indonesia with a population based on census 2010 reached 237.6 million people. If viewed from the supply side, current milk production in Indonesia is still very low, the number of dairy farmers around 118.75 thousand breeders. National dairy cow productivity stagnated, the average milk production ranges between 8-12 liters per day, with a scale of 2-3 maintenance per family breeder breeding. In addition, 90% of milk production resulting from farm people, so the quality and productivity cannot fulfill the demand of milk in the country, so most still have to import.